Urban Kampongs in Ambon: Whose Domain? Whose Desa? - Mearns, David (The Australian journal of anthropology, 1999)
A devastating fire in a poor quarter of the city of Ambon, Eastern Indonesia, provided the context in which a number of the social, cultural and historical factors shaping the lives of the city's residents came to the fore. The paper argues that to comprehend the experiences of people whose lives were touched by the fire, and to appreciate its significance, the meanings ascribed to the event, it is necessary to comprehend those multiple factors in all their complexity and interpenetration. The paper argues that the symbolic construction of urban space and its constitution as ‘place’ are continuously emergent out of processes which appear in transformational moments, such as this fire. Physical changes to the quarter through time are examined to demonstrate their relevance to understanding the contemporary social processes and their local interpretations. The migratory origins of the people; continuing divisions between Christian and Muslim populations; the ongoing relevance of ancestral spirits and magic; the role of colonial and postcolonial states, and Ambon's strategic position, are all argued to be important to understanding the meaning of the place and the use of space in the city. The implications of the intersection of at least four clusters of ideas about space and place are considered critical to any adequate account of the contemporary lives of Ambonese and to explaining how it comes to be that some residents can become permanently displaced. The argument emphasises the processual nature of the understandings of space in the urban context.